(3SjchdhLjI GdebGHdIs - (3HfLgGe(B, (3hGdJQaGfjcs; (3hHQhS ajcJhQehQ(B, s ((3GdbGgQI(B:s (3OGQ bHGA ddWHGYI h GdfTQ(B,s, 2002)
(3JLO aj gPG GdcJGH (B: (3GdaUd GdChd (B: (3eHGOF GhdjI(B-(3GdaUd GdKGfj (B: (3JYde GdebGHdI(B-(3GdaUd GdKGdK (B: (3ebGHdI GdWdGH(B-(3GdaUd GdQGHY (B: (3GdebGHdI aj NOeI GdJhGab Gdegfj (B( (3GdJhLjg Gdegfj (B)-(3GdaUd GdNGeS (B: (3GdHMK Yf hXjaI(B-(3GdaUd GdSGOS (B: (3ebGHdI GdeJbOejf ddhXGFa(B-(3GdaUd GdSGHY (B: (3GdGNJHGQ GdTagj aj ecGJH GdNOeI GdeOfjI(B-(3GdaUd GdKGef (B: (3GdGNJHGQ GdTagj (B( (3JcedI (B) (3JOQjH GdbGFejjf HGdebGHdI hGdHGMKjjf aj GdejOGf(B-(3GdaUd GdJGSY (B: (3ebGHdI GdYde HTG GdYdGbGJ Hjf GdeSJNOe hUGMH GdYed(B-(3GdaUd GdYGTQ (B: (3GSJaJGAGJ GdQCj GdYGe hGdeSM GdJLGQj GdTGed(B-(3GdaUd GdMGOj YTQ (B: (3ebGHdI Phj GdeTcdGJ (B: (3GdebGHdI aj af NOeI GdHTQ(B-(3GdaUd GdKGfj YTQ (B: (3ebGHdI Phj GdeTcdGJ (B: (3GdYjGOI GdfaSjI(B-(3GdaUd GdKGdK YTQ (B: (3GdebGHdI aj GdUMGaI(B-(3GdaUd GdQGHY YTQ (B: (3GdebGHdI GdNGUI HGdTgGOI GdbGfhfjI(B-(3GdaUd GdNGeS YTQ (B: (3GdNGJeIs
Keywords: (3GdJhXjas; (3GdebGHdIs